2013
DOI: 10.1088/0004-637x/772/1/21
|View full text |Cite
|
Sign up to set email alerts
|

Internal Gravity Waves in Massive Stars: Angular Momentum Transport

Abstract: We present numerical simulations of internal gravity waves (IGW) in a star with a convective core and extended radiative envelope. We report on amplitudes, spectra, dissipation and consequent angular momentum transport by such waves. We find that these waves are generated efficiently and transport angular momentum on short timescales over large distances. We show that, as in Earth's atmosphere, IGW drive equatorial flows which change magnitude and direction on short timescales. These results have profound cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
359
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(396 citation statements)
references
References 80 publications
34
359
2
1
Order By: Relevance
“…However, Be stars are very rapid rotators and stochastic excitation is enhanced in the presence of rapid rotation, through the Coriolis acceleration which modifies gravity waves. This has been demonstrated analytically by Mathis et al (2013) and observed in numerical simulations by Rogers et al (2013) …”
Section: Stochastic Excitation Of Pulsations In Be Starsmentioning
confidence: 55%
“…However, Be stars are very rapid rotators and stochastic excitation is enhanced in the presence of rapid rotation, through the Coriolis acceleration which modifies gravity waves. This has been demonstrated analytically by Mathis et al (2013) and observed in numerical simulations by Rogers et al (2013) …”
Section: Stochastic Excitation Of Pulsations In Be Starsmentioning
confidence: 55%
“…These IGWs are highly efficient at transporting angular momentum to the stellar surface (e.g., Rogers & Glatzmaier 2005;Rogers et al 2013). On the other hand, convection-driven IGWs are linked to the stochastic motion by the convective plumes escaping the convective core (e.g., Goldreich & Kumar 1990;Samadi et al 2010;Shiode et al 2013;Mathis et al 2014).…”
Section: The Pulsating Magnetic Hot Star Hd 43317mentioning
confidence: 99%
“…Meanwhile, a 1-σ detection of counter-rotation in a main-sequence B star (KIC 10526294, Triana et al 2015) appears to require even more elaborate angular momentum transport, but the observations are consistent with rigid rotation within 2 σ and the star's rotation period is also remarkably long at ∼ 188 d (Pápics et al 2014). Internal gravity waves could be responsible for these uniform or even counter-rotating profiles (Rogers et al 2013).…”
Section: Introductionmentioning
confidence: 99%